Słowiki, baśnie i dwugłowy orzeł. Mit imperium w li-teraturze rosyjskiej - Żejmo, Bożena (Przegląd Rusycystyczny, 2013)
Bożena Żejmo Uniwersytet Mikołaja Kopernika, Toruń, Poland bozena.zejmo@umk.pl СОЛОВЬИ, БАСНИ И ДВУГЛАВЫЙ ОРЕЛ. МИФ ИМПЕРИИ В РУССКОЙ ЛИТЕРАТУРЕ Резюме В основе данной статьи лежит представление о тесной взаимосвязи русской литера-туры XVIII–XX века и имперской идеологии. В XVIII веке попытки национально-госу-дарственной самоидентификации осуществлялись в значительной степени в опоре на опыт поэтической рефлексии о России, накопленный в те годы прежде всего авторами од. Оды Василия Петрова, Александра Сумарокова, Гавриила Державина — это не толь-ко система риторических фигур, но и определенная доктрина, которая глубоко проникла в общественно-политическую жизнь России. В XIX веке главным певцом имперской идеи был поэт и политический мыслитель Федор Тютчев, мечтающий о России как инкарнации Восточной Империи. Выработанные русскими литераторами стратегии формирования имперского самосознания продолжают современные писатели, прежде всего представители деревенской прозы. NIGHTINGALES, FAIRY TALES AND THE DOUBLE-HEADED EAGLE. THE MYTH OF EMPIRE IN RUSSIAN LITERATURE Summary The purpose of this article is to present the relationship between Russian literature and imperial ideology. In the eighteenth century, the attempts of nation-states to self-identifi-cation corresponded with the artistic visions of then poets. Odes written by such authors as Petrove, Sumarokov and Derzhavin represented doctrines, which played an important role in social and political life of Russia.In the nineteenth century the main eulogist of imperial idea was a poet and political thinker Fyodor Tyutchev, who dreamed of Tsarist Russia as an incarnation of the Empire of the East.The fall of the Soviet Union has created favorable circumstances for the mythological rebirth. Among the writers who have taken up the fight for the revival of the imperial Russian identity, distinguished themselves particularly representatives of “village prose” (Belov, Rasputin, Astafyev and Lichutin).